Stress resilience in young men mediates the effect of childhood trauma on their offspring's birth weight - An analysis of 250,000 families - Kristiina Rajaleid; Denny Vågerö (Elsevier, 2019)
Experiencing the death of a parent during childhood is a severe trauma that seems to affect the next generation's birth weight. We studied the consequences of parental loss during childhood for men's psychological and physiological characteristics at age 18, and whether these were important for their first-born offspring's birth outcomes. We used a structured life-course approach and four-way decomposition analysis to analyse data for 250,427 three-generation families retrieved from nationwide Swedish registers and found that psychological resilience was impaired and body mass index was higher in men who had experienced parental death. Both characteristics were linked to offspring birth weight. This was lower by 18.0 g (95% confidence interval: 5.7, 30.3) for men who lost a parent at ages 8-17 compared to other ages. Resilience mediated 40% of this influence. Mediation by body mass index, systolic and diastolic blood pressure was negligible, as was the effect of parental loss on length of gestation. There was no mediation by the education of the men's future spouse.Previous literature has indicated that the period before puberty, the "slow growth period", is sensitive. Our evidence suggests that this may be too narrow a restriction: boys aged 8-17 appear to be particularly likely to respond to parental loss in a way which affects their future offspring's birth weight. We conclude that the observed transgenerational influence on birth weight is mediated by the father's psychological resilience but not by his body mass index or blood pressure.